Estudo da integração da cadeia de suprimentos da indústria siderúrgica - Alvaro Simoes da Conceicao Neto (2005)
The search for efficiency has motiveted many companies to develop the management of the inventories and service levels. In this context, demand forecast had became a challenging goal, once the information from the supply chain are subject to variability and distortions. This work consists on the evaluation of the bullwhip effect - increase in demand variability as one moves up the supply chain away from the customer - in the supply chain of a multinational steel company, with a heavy performance in the Brazilian domestic market. It also evaluates in which conditions the distortions occur and the strategies used to remedy them. The companies analyzed were distributors and consumers of the civil construction product lines. A survey methodology was applied, with a questionnaire sent to these companies by e-mail and the results analyzed with statistics tools.